THE MUSLIM ARCHITECTURE: DURING SULTANATE PERIOD IN KASHMIR - Dr Nadia Mehrdin; Toheeda Begum; Sania Siraj (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2023)
This paper delves into the distinctive architectural evolution during the Sultanate period in Kashmir, a pivotal era that witnessed the infusion of Islamic influences into the region’s indigenous architectural traditions. Spanning from the early 14th to the mid-16th century, this epoch marked a significant transition in the architectural landscape of Kashmir, as it transitioned from Hindu rule to Islamic governance under various sultanates. The research employs a multidisciplinary approach, drawing from historical records, archaeological evidence, architectural analysis, and artistic interpretations to shed light on the key features, innovations, and socio-cultural implications of Muslim architecture in Kashmir. It explores the fusion of Persian, Central Asian, and indigenous Kashmiri architectural elements, resulting in a unique synthesis that defined the aesthetic character of the region. The paper also investigates the socio-political factors that catalyzed this architectural transformation, examining how the arrival of Muslim rulers influenced building practices, spatial organization, and the establishment of new urban centers. Special attention is given to notable architectural landmarks such as mosques, tombs, forts, and palaces that exemplify the architectural prowess of the period.